COMBINED APPLICATION OF DISTILLERY SPENT WASH, BIO-COMPOST AND INORGANIC FERTILIZERS IMPROVES GROWTH, YIELD AND QUALITY OF WHEAT - M. U. Chattha; H. Ali; M. Umer Chattha; M. U. Hassan; M. B. Chattha; M. Nawaz; S. Hussain (Journal of Animal and Plant Sciences, 2018)
The combined application of organic and inorganic fertilizer improves crop productivity and soil health. The field experiments were conducted to determine the effect of distillery spent wash (DS), bio-compost (BC) and NPK fertilizers on growth, yield and quality of wheat crop during 2013-14 and 2014-15 at Shakarganj Sugar Research Institute (SSRI) Jhang, Pakistan. The experiment was laid out in randomized complete design and composed of different combination of 3 -1 DS, BC and NPK i.e., T : DS 0%+ BC 0% + F 0%, T : DS 50% (64m ) + BC 50% (450kg ha ) + F 0%, T : DS 50% + 1 2 3 -1 -1 3 -1 BC 50% (450kg ha ) + F 25% (30-25-15 NPK kg ha ), T : DS 25% (32 m ) + BC 25% ( 225kg ha ) + F 50% ( 60-50- 4 -1 3 -1 -1 3 30 NPK kg ha ), T : DS 50 % (64m ) + BC 25 % (225kg ha ) + F 25 % ( 30-25-15 NPK kg ha ), T : DS 25% (32 m ) + 5 6 -1 -1 BC 50% ( 450kg ha ) + F 25% ( 30-25-15 NPK kg ha ). The maximum improvement in growth attributes were recorded in treatment T , whereas, the minimum values of growth attributes were found in control treatment. The maximum plant 4 -1 height ( 107 cm, 106.2 cm), productive tillers (427.50, 424.25) , 1000 grain weight (37 g, 37.75 g) grain yield (5.15 t ha , -1 -1 -1 4.96 t ha ) and biological yield (10.28 t ha , 10.14 t ha ) were recorded in treatment T while the minimum values of 4 these attributes were obtained without use of DS, BC and NPK. Moreover, maximum grain nitrogen, phosphorus, potassium and protein contents were also found in treatment T whereas no application of DS, BC and NPK significantly 4 3 - reduced these qualitative attributes. These results suggested that combination of [(DS 25% (32 m )+BC 25% (225kg ha 1 -1 )+F 50% ( 60-50-30 NPK kg ha )] can be used to improve growth, yield and quality of wheat. 2008). The continuous use of in inorganic fertilizers also
Keywords: Wheat; Bio-compost; Distillery spent wash; NPK; Growth; Yield; Quality.